The association between supraorbital ethmoid air cells and orbital proptosis in patients with chronic rhinosinusitis. Issue 2 (27th August 2012) - Comer, Brett T.; Kincaid, Nathan W.; Kountakis, Stilianos E.
<x xml:space="preserve">Abstract</x> Background Orbital proptosis is a known possible complication in patients with chronic rhinosinusitis (CRS). This study was undertaken to determine the association of sinus anatomy and anatomic variants with the predisposition for such a complication. All adult patients (n = 16) with orbital proptosis were identified from a prospectively‐collected database at a tertiary institution. These were compared with a series of randomly‐selected patients (n = 50) diagnosed with chronic sinusitis and who had undergone sinus computed tomography. The presence or absence of supraorbital ethmoid air cells (SOECs) was noted and compared between the 2 groups. The primary sinus anatomy responsible for the proptosis was also identified. Statistical analysis was performed using the chi squared test. Sixteen patients with orbital proptosis were identified, of which all but 1 had SOECs present. Causal analysis showed that in all but 1 case the SOECs were the cause of proptosis. Of the 50 patients with CRS but without proptosis, only 13 had SOECs present and 37 patients did not (chi squared = 22.8, p = 0.000002). SOECs appear to be highly associated with and most often are responsible for orbital proptosis in patients with CRS. © 2012 ARS–AAOA, LLC. Methods All adult patients (n = 16) with orbital proptosis were identified from a prospectively‐collected database at a tertiary institution. These were compared with a series of randomly‐selected patients (n = 50) diagnosed with chronic sinusitis and who had undergone sinus computed tomography. The presence or absence of supraorbital ethmoid air cells (SOECs) was noted and compared between the 2 groups. The primary sinus anatomy responsible for the proptosis was also identified. Statistical analysis was performed using the chi squared test. Sixteen patients with orbital proptosis were identified, of which all but 1 had SOECs present. Causal analysis showed that in all but 1 case the SOECs were the cause of proptosis. Of the 50 patients with CRS but without proptosis, only 13 had SOECs present and 37 patients did not (chi squared = 22.8, p = 0.000002). SOECs appear to be highly associated with and most often are responsible for orbital proptosis in patients with CRS. © 2012 ARS–AAOA, LLC. Results Sixteen patients with orbital proptosis were identified, of which all but 1 had SOECs present. Causal analysis showed that in all but 1 case the SOECs were the cause of proptosis. Of the 50 patients with CRS but without proptosis, only 13 had SOECs present and 37 patients did not (chi squared = 22.8, p = 0.000002). SOECs appear to be highly associated with and most often are responsible for orbital proptosis in patients with CRS. © 2012 ARS–AAOA, LLC. Conclusion SOECs appear to be highly associated with and most often are responsible for orbital proptosis in patients with CRS. © 2012 ARS–AAOA, LLC.